Crystal structure of diethyl 2,2′-[((1E,1′E)-{[(1R,4R)-cyclohexane-1,4-diyl]bis(azanylylidene)}bis(methanylylidene))bis(1H-pyrrole-2,1-diyl)]diacetate - Alshawi, Jasim (Acta Crystallogr E Crystallogr Commun, 2015)
The whole molecule of the title compound, C(24)H(32)N(4)O(4), is generated by inversion symmetry. The cyclohexane ring adopts a chair conformation and the conformation about the C=N bonds is E. The pyrrole rings have an anti confirmation with respect to the cyclohexane moiety and the ethyl acetate groups have extended conformations. In the crystal, molecules are linked by pairs of C—H⋯O hydrogen bonds forming chains, enclosing R (2) (2)(10) ring motifs with inversion symmetry, propagating parallel to the (101) plane.